Indian Penal code: Bare act with short notes (New Delhi, 2015)
The IndianPenal Code (45 of 1860) as ammended by the Criminal Law (Amendemnent) Act, 2013 (13 of 2013) with State Amendments and Classification of Offences, State Amendment Index and Subject Index
Keywords: Penal code